Denture Adhesives – Best Practice. (1st January 2020) - Jagger, Robert; King, Elizabeth
Abstract : Looseness of dentures is a common complaint and can cause patients embarrassment and distress. Looseness is often associated with ill-fitting dentures, but some patients with technically excellent dentures may complain of looseness as a result of, for example, severely resorbed alveolar ridges, lack of saliva or poor adaptive ability. Recommendations for effective use of denture adhesive that can be given to patients by the dental team are provided. CPD/Clinical Relevance: The dental team needs to explain effective approaches to the use of denture adhesives to patients. Written information can help to reinforce best practice.